Caspase-3 serves as an intracellular immune receptor specific for lipopolysaccharide in oyster Crassostrea gigas. (August 2016) - Xu, Jiachao; Jiang, Shuai; Li, Yiqun; Li, Meijia; Cheng, Qi; Zhao, Depeng; Yang, Bin; Jia, Zhihao; Wang, Lingling; Song, Linsheng
Abstract: Apoptosis is a form of programmed cell death process controlled by a family of cysteine proteases called caspases, which plays a crucial role in the immune system homeostasis. The apoptosis and the detailed regulation mechanism have been well studied in vertebrate, but the information in lower animals, especially invertebrates, is still very limited. In the present study, Caspase-3 in the Pacific oyster Crassostrea gigas (designated Cg Caspase-3) was enriched by lipopolysaccharide (LPS) affinity chromatography and further identified by MALDI-TOF/TOF-mass spectrometry. The binding activity of Cg Caspase-3 to LPS was confirmed by enzyme-linked immunosorbent assay, and surface plasmon resonance analysis revealed its high binding specificity and moderate binding affinity ( K D = 1.08 × 10 −6 M) to LPS. The recombinant Cg Caspase-3 exhibited high proteolytic activity to substrate Ac-DEVD- p NA and relatively weak activity to substrate Ac-DMQD- p NA and Ac-VDQQD- p NA. The binding of Cg Caspase-3 to LPS significantly inhibited its proteolytic activity toward AC-DEVD- p NA in vitro . The over-expression of Cg Caspase-3 leaded to the phosphatidylserine exposure on the external plasma membrane and the cleavage of poly (ADP-ribose) polymerase, which reduced cell viability, and finally induced cell apoptosis. But the cell apoptosis mediated by Cg Caspase-3 in vivo was significantly inhibited by the treatment of LPS. These results collectively indicated that Cg Caspase-3 could serve as an intracellular LPS receptor, and the interaction of LPS with Cg Caspase-3 specifically inhibited the cell apoptosis induced by Cg Caspase-3. Highlights: Cg Caspase-3 directly binds to LPS with high specificity. Cg Caspase-3 exhibits caspase activity and induces cell apoptosis in vivo . The N-terminal is necessary to LPS binding activity and proteolysis of Cg Caspase-3. Intracellular LPS specifically inhibited cell apoptosis induced by Cg Caspase-3.